2021
DOI: 10.1136/bmjdrc-2020-001905
|View full text |Cite
|
Sign up to set email alerts
|

Glucolipotoxicity and GLP-1 secretion

Abstract: IntroductionThe concept of glucolipotoxicity refers to the combined, deleterious effects of elevated glucose and/or fatty acid levels.Research design and methodsTo investigate the effects of chronic glucolipotoxicity on glucagon-like peptide-1-(7-36) amide (GLP-1) secretion, we generated glucolipotoxic conditions in human NCI-H716 enteroendocrine cells using either 5 or 25 mM glucose with or without 500 µM palmitate for 72 hours. For in vivo study, we have established a chronic nutrient infusion model in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Deletion of Scd1 reduces the synthesis of oleic and palmitoleic acids and thus prevents the accumulation of lipids in cells [ 51 ]. A recent study has shown that glucolipotoxic conditions can reduce GLP-1 secretion [ 52 ]; therefore, increased levels of intracellular lipids may be detrimental to GLP-1 secretion. In support of this, whole-body knockout of Scd1 results in the accumulation of lipids in the liver, causing hepatic steatosis and hyperlipidaemia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Scd1 reduces the synthesis of oleic and palmitoleic acids and thus prevents the accumulation of lipids in cells [ 51 ]. A recent study has shown that glucolipotoxic conditions can reduce GLP-1 secretion [ 52 ]; therefore, increased levels of intracellular lipids may be detrimental to GLP-1 secretion. In support of this, whole-body knockout of Scd1 results in the accumulation of lipids in the liver, causing hepatic steatosis and hyperlipidaemia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues in 2018 found that diabetic patients with dyslipidemia have impaired GLP-1 secretion that directly correlated with lipotoxicity [ 88 ]. Moreover, GLP-1 secretion may be increased in response to lipotoxicity and dyslipidemia in an effort to mitigate them [ 89 ]. In summary, incretin-based medications have pharmacological properties that enable them to inhibit lipotoxicity and thereby help to prevent lipotoxicity-dependent disorders, especially renal and cardiovascular complications [ 90 ].…”
Section: Incretins and Lipid Homeostasismentioning
confidence: 99%
“…T2DM is characterized by pancreatic β-cell dysfunction and insulin resistance. It has been shown that chronic hyperglycemia leads to the decrease of insulin biosynthesis and secretion due to β-cell glucose toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and that the reduction of insulin mRNA expression is accompanied by decreased nuclear expression of insulin transcription factors such as MafA and PDX-1 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Such phenomena are known as β-cell glucose toxicity.…”
Section: Incretin and Pancreatic β-Cellsmentioning
confidence: 99%